How does analysts' forecast quality relate to corporate investment efficiency? - Chen, Jonas Tao (2017)
We examine the impact of financial analysts on the efficiency of firms’ investment decisions. We use the accuracy and dispersion of financial analysts’ earnings forecasts as proxies of analyst expertise and quality in making forecasts. We find that high quality forecast is associated with higher investment if the firm is more likely to under-invest and lower investment if the firm is more likely to over-invest, suggesting that forecast quality increases firm-level investment efficiency. We further show that such effects are stronger for the firms with higher information asymmetry and lower institutional stock ownership. The results are consistent with the notion that higher quality of analyst forecasts increases the information environment and external monitoring, which in turn increases investment efficiency.